(untitled) (Journal of the College of Education for Women, 2019)
This research deals with the study of types of parallelism in contemporary Arabic poetry and took the hair Mahmoud Darwish, a model for the study has been the goal of research to clarify the term parallelism and the statement of the most important types, said evidence of that in the poetry of Mahmoud Darwish